2017
DOI: 10.1200/jco.2017.35.15_suppl.559
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary breast conservation patient outcomes for ductal carcinoma in situ and margins < 2 mm.

Abstract: 559 Background: Recent national consensus guidelines regarding optimal margin width for the management of DCIS have been published; however, controversy remains for managing margins <2mm. The relationship between margin width and locoregional recurrence (LRR) was determined in a contemporary cohort of patients. Methods: 1504 patients with DCIS undergoing definitive breast conserving surgery from 1996 to 2010 were analyzed for clinical and pathologic characteristics from a prospectively managed comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A different perspective comes from the American Society of Breast Surgeons that considers exclusively "no ink on the tumor" as a negative margin [33]. Notably the MD Anderson experience [34], corroborated by the Memorial Sloan Kettering Cancer Center [35], reported that the difference in Local recurrence rate (LRR) for patients with margins <2 mm vs. ≥ 2 mm (10-year LRR 30.9% vs. 5.4%, respectively; p = 0.003) was abrogated in patients receiving radiotherapy (10-year LRR 4.8% vs. 3.3%, respectively; p = 0.72). As many authors state that the strongest predictor of local recurrence of DCIS after BCS is a positive surgical margin at the time of initial surgery, a careful macroscopic sampling and microscopic examination must be carried out.…”
Section: Surgical Marginsmentioning
confidence: 99%
“…A different perspective comes from the American Society of Breast Surgeons that considers exclusively "no ink on the tumor" as a negative margin [33]. Notably the MD Anderson experience [34], corroborated by the Memorial Sloan Kettering Cancer Center [35], reported that the difference in Local recurrence rate (LRR) for patients with margins <2 mm vs. ≥ 2 mm (10-year LRR 30.9% vs. 5.4%, respectively; p = 0.003) was abrogated in patients receiving radiotherapy (10-year LRR 4.8% vs. 3.3%, respectively; p = 0.72). As many authors state that the strongest predictor of local recurrence of DCIS after BCS is a positive surgical margin at the time of initial surgery, a careful macroscopic sampling and microscopic examination must be carried out.…”
Section: Surgical Marginsmentioning
confidence: 99%
“…We recently updated this cohort with additional patients and longer follow-up and analyzed outcomes. We identified 1,491 patients with DCIS undergoing definitive BCS from 1996 to 2010 14 , 15 . Cox proportional hazard models were used to examine the relationship between margin width (< 2 mm or ≥ 2 mm) and local - regional recurrence (LRR) by receipt of adjuvant radiation therapy (RT).…”
Section: Anderson Contemporary Outcomes Of Bcs For Dcis and Marginmentioning
confidence: 99%
“…Radiopaque clips are placed routinely in the resection cavity to facilitate identification of the area for radiation therapy and to facilitate the use of a boost when indicated. Although the median size of DCIS cases treated with BCS over the past 20 years at MD Anderson is only 1 cm, during the same time period the use of oncoplastic surgery has allowed for an increasing number of patients with an unfavorable tumor location to become BCS-eligible 14 , 32 . Essentially, if all malignant appearing calcifications can be removed utilizing this approach and the margins are negative, there is no absolute size criteria utilized at our institution for the selection of patients for BCS in the treatment of DCIS.…”
Section: Surgical Technique and Considerationsmentioning
confidence: 99%
See 2 more Smart Citations